Indonesian foodstuffs in facing global food crisis: Economic aspects of soybean farming - Fachrur Rozi; Herman Subagio; Dian Adi Anggraeni Elisabeth; Lyli Mufidah; Moh Saeri; Supriyadi; Rusli Burhansyah; Juliana Carolina Kilmanun; Ruly Krisdiana; Zainuri Hanif; Ernany Dwi Astuty; Rumanintya Lisaria Putri (Journal of Agriculture and Food Research)
The dynamic of the current global food situation is raising concerns about a potential food crisis in the future. This implies that food production must increase. However, in practice, the availability of agricultural land is increasingly limited. Soybean, as a food commodity, is not exempt from this issue. This paper explores the microeconomic and macroeconomic aspects of soybean farming in preparing future global food. The study of microeconomic aspects of farming includes soybean farmers' behaviour using principal component analysis (PCA) approach. Meanwhile, the macroeconomic aspects are analyzed using structural equation modelling (SEM) with Smart PLS software. The research findings identified four key variables with a high level of urgency, as indicated by the PCA factor loadings on the microeconomic aspect of farmers' behaviour in addressing the volatility of the soybean food supply. These variables are market formation, food security guarantees, productivity enhancement, and pricing. Based on bootstrapping and path coefficient of inflation in the PLS-SEM analysis for soybean commodities, the impact of inflation was found to significantly affect farmers' income and the demand for soybeans on the macroeconomic side. Indirectly, inflation also impacts exchange rates and soybean prices through income variables. Additionally, inflation indirectly affects soybean prices, population size, and consumption levels through the demand variable. Therefore, the volatility caused by inflation in the soybean commodity market can be mitigated by ensuring a stable domestic soybean supply or reducing imports.